Complexes of lead(II) perchlorate and hexafluorophosphate with aromatic amine N-oxides - Chiericato Júnior, Glaico; de Giovani, Wagner Ferraresi; Garla, Luiz Carlos; Betarello, Virginia Helena (Eclética Química, 1989)
.